Is the Tongue an “Alternative Donor Site for Anterior Urethroplasty”? (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the effectiveness of a lingual mucosal graft (LMG) urethroplasty for long segment (>2cm) anterior urethral strictures.Materials and Methods: A total of 30 patients underwent urethroplasty for anterior urethral strictures using dorsal onlay of a LMG from January 2009 to December 2010. We selected 21 to 56 years old (mean age 36.6). Stricture length was 22 to 59 mm (mean 36); 14 strictures were in the bulbar urethra, 09 were in the proximal penile and 07 were in both bulbar and penile urethra. Postoperatively all patients were followed with urethrography, uroflowmetry, cystourethrography and urethroscopy after 3weeks, 3 months and 06 months. Successful reconstruction criteria were peak flow rate greater than 15 ml per second and no need for postoperative urethral dilation.Results: The mean period of follow-up was 9 months (range 4-12). The overall success rate at 3rd week and 3rd month was 96.7% and at 6th month was 90%. Three patients developed repeat stricture at the anastomotic site. All the patients were able to resume oral fluid within 24 h, eat soft solid diet in 48–72 h and return to normal diet after 4– 5 days of surgery. No patient suffered from difficulty in opening the mouth, salivation disturbances, or difficulty in protrusion of tongue.Conclusions: LMG is easy to harvest. LMG seems to be associated with less postoperative pain and a minor risk of donor site complications or without any functional or esthetic deficiency. The tongue may be the best alternative donor site.Bangladesh Journal of Urology, Vol. 15, No. 1, Jan 2012 p.11-14